Comparison of the Results in the Ambiguity Resolution for a Network of GNSS Stations in Europe Using GPS Data and the Combination with GLONASS Data, Using the Bernese GNSS Processing Software - Paniagua-Jiménez, Diana; Valverde-Calderón, Jose (Uniciencia, 2017)
The parameters of the ambiguity in the original observation equations are integer numbers. Technically two procedures are necessary to fix the ambiguities: first, the parameters are estimated as real values; in the second step, they are set to integers. Fixing the ambiguities decreases the number of parameters to be estimated in the final adjustment of the network, taking this result in a reduction in the number of items stored in memory, in the time investing in the processing and an improvement in the quality of the calculate of  coordinates. It was made the comparative analysis between the results after processing the network two times: in the first one, only GPS observation was processed; in the second one, both GPS and GLONASS observations were processed. The network used in the project has 25 GNSS stations, located in Europe. The processing was made using the Bernese GNSS software version 5.2. The main conclusion is the importance in the selection of the ambiguity strategy due to is a topic that require an complete analysis, due to the impact that the choose computation method have in the finals results and in the processing time.